Gender Discrimination in Artificial Intelligence: An International Human Rights Law Perspective and the Quest for Binding Regulation - Ayu Riska Amalia; Diva Pitaloka; Adhitya Nini Rizki Apriliana (Unram Law Review, 2025)
Artificial intelligence (AI) has transformed and reshaped the way people work and interact. While AI provides convenience, it also poses significant challenges to human rights, particularly gender equality. The use of AI in recruitment processes, healthcare diagnosis, and discriminatory content moderation illustrates how it can exacerbate existing inequalities. This study employs a normative juridical method with a qualitative approach, analyzing primary instruments of international human rights law such as the Universal Declaration of Human Rights (UDHR),the International Covenant on Civil and Political Rights (ICCPR), the International Covenant on Economic, Social and Cultural Rights (ICESCR), and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). It also examines non-binding frameworks, namely the UNESCO Recommendation on the Ethics of AI and the OECD AI Principles, and compares them with the binding EU AI Act. The findings indicate that AI has the potential to violate fundamental rights of women, including the rights to equality and non-discrimination, work, privacy, health, participation in public and political life, as well as representation and identity. Furthermore, soft-law mechanisms remain insufficient to prevent gender bias, as their implementation relies heavily on states’ political will. Nevertheless, states have a positive obligation under international law to respect, protect, and fulfil the right to equality; thus, a binding international legal framework is urgently needed to ensure accountability and gender-sensitive AI governance.